1997
DOI: 10.1074/jbc.272.2.952
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Specific Substrate Sequence Motifs of Protein Kinase C Isozymes

Abstract: Protein kinase C (PKC) family members play significant roles in a variety of intracellular signal transduction processes, but information about the substrate specificities of each PKC family member is quite limited. In this study, we have determined the optimal peptide substrate sequence for each of nine human PKC isozymes (␣, ␤I, ␤II, ␥, ␦, ⑀, , , and ) by using an oriented peptide library. All PKC isozymes preferentially phosphorylated peptides with hydrophobic amino acids at position ؉1 carboxyl-terminal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
475
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(499 citation statements)
references
References 32 publications
24
475
0
Order By: Relevance
“…A role for Cetrorelix in the stimulation of PKC activity was determined by phosphorylation of the MARCKS substrate for classical and novel PKC isoforms or by probing for generalised increased phosphorylation of canonical PKC target serines (Figure 3) (Fujise et al, 1994;Nishikawa et al, 1997). This was further confirmed through the use of chelerythrine, a pan-PKC inhibitor (Wells et al, 2002), to prevent such phosphorylation (data not shown).…”
Section: Reversal In Adhesion Molecule Profile Is Related To Egfr Sigmentioning
confidence: 92%
“…A role for Cetrorelix in the stimulation of PKC activity was determined by phosphorylation of the MARCKS substrate for classical and novel PKC isoforms or by probing for generalised increased phosphorylation of canonical PKC target serines (Figure 3) (Fujise et al, 1994;Nishikawa et al, 1997). This was further confirmed through the use of chelerythrine, a pan-PKC inhibitor (Wells et al, 2002), to prevent such phosphorylation (data not shown).…”
Section: Reversal In Adhesion Molecule Profile Is Related To Egfr Sigmentioning
confidence: 92%
“…PKD preferentially targets residues within sequences containing a basic residue at -3 as well as a leucine at the -5 position in model peptide substrates [14,20].…”
Section: Pkd Does Not Phosphorylate C-jun At Jnk Target Sitesmentioning
confidence: 99%
“…PKCs preferentially phosphorylate substrates that contain a serine/threonine in the context of adjacent amino acids, with different isoforms preferring particular amino acids that surround the phosphorylation site [3,4]. All PKC isoforms share a similar overall structure in that they consist of an N-terminal regulatory domain that is coupled to a highly conserved C-terminal kinase domain ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%